2020
DOI: 10.1016/j.envres.2020.110001
|View full text |Cite
|
Sign up to set email alerts
|

Potential link between compromised air quality and transmission of the novel corona virus (SARS-CoV-2) in affected areas

Abstract: The emergence of a novel human corona virus disease (COVID-19) has been declared as a pandemic by the World Health Organization. One of the mechanisms of airborne transmission of the severe acute respiratory syndrome - corona virus ( SARS-CoV-2 ) amid humans is through direct ejection of droplets via sneezing, coughing and vocalizing. Nevertheless, there are ample evidences of the persistence of infectious viruses on inanimate surfaces for several hours to a few da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…Our data found that PM 2.5 , NO 2 , CO and SO 2 were associated with the number of daily confirmed cases in two main clusters of COVID‐19 infection cases in Korea differently. Results from spatial analyses have consistently shown the rapid spread of COVID‐19 in highly polluted areas of the US, Italy, Spain and China [41]. Different findings in the context of Korea could be explained by the sufficiently lower levels of air pollutants than many other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Our data found that PM 2.5 , NO 2 , CO and SO 2 were associated with the number of daily confirmed cases in two main clusters of COVID‐19 infection cases in Korea differently. Results from spatial analyses have consistently shown the rapid spread of COVID‐19 in highly polluted areas of the US, Italy, Spain and China [41]. Different findings in the context of Korea could be explained by the sufficiently lower levels of air pollutants than many other areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to humans as the source of ambient aerosol transmission, TSDF (hazardous waste treatment, storage and disposal facilities) and RMP (Risk Management Plan) sites are potential air pollution sources ( Hendryx and Luo, 2020 ; Tung et al, 2021 ). Under certain conditions, ambient aerosols, such as water-borne aerosols, can provide favorable surfaces for the adsorption of organic molecules and viruses, and facilitate higher transmission rate under certain ambient conditions ( Manoj et al, 2020 ). Polluted water can be a source of viruses, and aerosols from this source can carry a variety of viruses, leading to a higher exposure rate for residents living around the contaminated area ( Rocha-Melogno et al, 2020 ).…”
Section: Influence Of Ambient Aerosols On the Transmission Of Covid-1mentioning
confidence: 99%
“…Some studies suggested a possible relation of virus outbreak with high levels of environmental air pollution (Barcelo, 2020;Bashir et al, 2020;Copat et al, 2020;Filippini et al, 2020;Li et al, 2020;Ogen, 2020;Pequeno et al, 2020;Setti et al, 2020b;Tsatsakis et al, 2020;Wu et al, 2020;Zhu et al, 2020). Putative mechanisms included enhanced susceptibility to respiratory viral infections through damage and inflammation of lung cells, immune dysregulation, and hyperactivation of inflammatory cytokines and chemokines (Chen et al, 2010;Comunian et al, 2020;Conticini et al, 2020;Peng et al, 2020), upregulation of viral receptor ACE-2 (Borro et al, 2020;Tung et al, 2020), or air pathogen transportation by particulate matter suitable as virus carrier (Comunian et al, 2020;Manoj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%